Plataforma de Brazos Robóticos de Tecnología Abierta para realizar Experiencias de Laboratorio de Control de Posición, Planificación de Trayectoria y Control de Visión Artificial - Borja Borja, Mario (2016)
The main problem in the development of specialization courses in robotics in our country is that there are no laboratories with robotic arms that allow testing positioning control, path planning and control with artificial vision and generally in academic settings is done experiments using software simulation.In this paper an alternative to enhance learning in the study control robotic arms using real robotic arms with an open technology platform software and hardware that allows students to modify programs to implement control algorithms position it is proposed joints, path planning and control with artificial vision. The proposal is to develop the full technology control system of the robotic arms on the basis of the analysis of the requirements of electronic and computer system the selection of power electronics, industrial computers based on digital signal controller (DSC), a computer personnel to user interface.Develop the core software for industrial computer and basic software for the PC that allows load programs online through the serial port from a personal computer and also a user interface on the computer that can be modified according to the need and used as control system upper level that performs calculations path planning, inverse problem and other high-level systems with artificial vision control. As a result the open technology platform that includes hardware and software for robotic arms up to six degrees of freedom with DC motors in the joints of up to 100 watts, encoders and sensors to run was obtained. The platform was tested with the mechanics of serial robotic arm Mitsubishi RV-M1 compliant electronic and construction parameters required by the prototype.